Pipelines, petitions, and protests in the Internet Age: Exploring the human geographies of online petitions challenging proposed transcontinental Alberta Oil Sands pipelines - McNeill, J; Thornton, T (Taylor and Francis, 2017)
Since the mid-2000s, millions of spatiotemporally disparate and demographically heterogeneous North Americans have signed online petitions challenging proposed transcontinental Alberta oil sands export pipelines. This phenomenon typifies bottom-up, self-organized, and ostensibly extemporaneous cyberactivism. These dynamics contradict traditional theoretical assumptions about rational choice and social pressures in collective action, birthing queries regarding why individuals participate. Human geographies comprising three online petitions challenging separate proposed pipelines are accordingly examined by comparing signatories' stated sociopolitical motivations for signing with their corresponding geospatial distributions. This innovative fusion of qualitative and quantitative research methods was designed to explore hetero versus homogeneity in signatories' sociopolitical commitments and locations. The results empirically corroborate Bennett and Segerberg's (2012) thesis that cyberactivism is governed by a unique logic of connective action wherein participation thresholds are low, collective identities and social incentives are weak, relationships are defined socially rather than spatially, and contentious politics are highly personalized. Four integrated findings with implications for policymaking and future research are offered for consideration.